Co-Leadership (Co-LEAD) Model Based on Behavioral Competence Transformation (BCT) to Improve Cooperative Performance and Collaboration in Lamongan - Rudi Wibowo; Devi Febrianti; Ira Megasyara; Nuning Nurna Dewi; Aprelia Nur Kumalasari; Imran Syah; Minullah Minullah (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the implementation of the Co-Leadership (Co-LEAD) model based on Behavioral Competence Transformation (BCT) in improving the performance and collaboration of cooperative teams in Lamongan Regency. The observed phenomenon is the low level of collaboration and the dominance of individualistic leadership that hinders organizational effectiveness. The study used a qualitative interpretive approach with case studies in three cooperatives, namely KUD Minatani, KUD Tani Mulyo, and KPRI Handayani. Data were collected through in-depth interviews, observation, and documentation. The results show that the implementation of BCT-based Co-Leadership consistently improves the quality of collaboration and organizational performance. Empirically, the findings indicate an increase in member involvement in decision-making (marked by the active participation of all administrators in strategic forums), an increase in the intensity of communication and coordination between administrators, and an increase in operational efficiency reflected in the acceleration of administrative task completion and more transparent and accountable financial management. In addition, a more equitable distribution of roles contributes to increased organizational responsiveness to member needs and a strengthened sense of ownership among cooperative administrators and members. Theoretically, this study makes a significant contribution to the development of collaborative leadership literature by offering a conceptual integration between Co-Leadership and Behavioral Competence Transformation as behavioral mechanisms that explain the relationship between collective leadership structures and improved team performance. This study expands the study of shared leadership by emphasizing that the effectiveness of Co-Leadership is not only determined by role distribution, but also by behavioral competency transformation that includes aspects of communication, collective decision-making, and conflict resolution. These findings enrich the academic discourse by providing a contextualized behavior-based model in community-based cooperative organizations, which was previously limited in the literature.